TG-DTG-DSC, FTIR, DRIFT and Py-GC-MS studies of thermal decomposition for poly(sodium acrylate)/dextrin (PAANa/D) – new binder BioCo3 - Grabowska, Beata; Kaczmarska, Karolina; Bobrowski, Artur; Żymankowska-Kumon, Sylwia; Kurleto-Kozioł, Żaneta (Journal of Casting & Materials Engineering, 2017)
TG-DTG-DSC, FTIR, DRIFT, and Py-GC-MS studies have been conducted to determine the effect of the thermal decompositionconditions and structure of foundry binder BioCo3 in the form of a composition poly(sodium acrylate)/dextrin(PAANa/D) on the progress of degradation in terms of processes occurring in foundry sands in contact with liquid metal.TG-DTG-DSC curves of the composition allowed us to determine the temperature range in which they do not undergodegradation, by which they do not lose their binding properties. With temperature increasing, physical and chemicalchanges occur that are related to the evaporation of solvent water (20–110°C), followed by the release of constitutionwater, and finally intermolecular dehydration (110–230°C). In this temperature range, processes that are mainly reversibletake place. Within a temperature range of 450–826°C, polymer chains are decomposed, including the decompositionof side chains. Within a temperature range of 399–663°C, polymer composition decomposition can be observed (FTIR,DRIFT), and gas products are generated from this destruction (Py-GC-MS).